Penerapan Model Pembelajaran Berbasis Think-Talk-Write (TTW) Untuk Meningkatkan Kemampuan Berpikir Logis Pada Siswa - Bambang Bambang (Departement of Mathematics Education, 2021)
The Think Talk Write (TTW) based learning model in school action research is applied to material regarding math problems in everyday life. The research was carried out with the aim of knowing whether the application of the Think Talk Write (TTW) based learning model for students of SD Negeri Wonokusumo VII / 46 Surabaya could improve their logical thinking skills in Mathematics. The research was conducted with a two-cycle action mechanism. And based on the results of the analysis, it can be concluded that the application of the Think Talk Write (TTW) based learning model can improve logical thinking skills and improve student achievement at SD Negeri Wonokusumo VII / 46 Surabaya. This can be seen from the increase in students' logical thinking skills in improving their learning outcomes. The effectiveness of the application of the Think Talk Write (TTW) based learning model in improving student achievement of SD Negeri Wonokusumo VII / 46 is shown through an increase in the average post-test score, an increase in the percentage of classical completeness and an increase in the value of observations on students' logical thinking abilities. The average post-test score in cycle I was 74.25 and cycle II was 78.29. Classical completeness in cycle I 76% and cycle II 91%. The average value of observations on students' logical thinking skills in the first cycle is 79.59 and the second cycle is 82.4.